Altered Patterns of Reflex Excitability, Balance, and Locomotion Following Spinal Cord Injury and Locomotor Training - Bose, Prodip K.; Hou, Jiamei; Parmer, Ron; Reier, Paul J.; Thompson, Floyd J. (Frontiers in Physiology, 2012)
Spasticity is an important problem that complicates daily living in many individuals with SCI. While previous studies in human and animals revealed significant improvements in locomotor ability with treadmill locomotor training, it is not known to what extent locomotor training influences spasticity. In addition, it would be of considerable practical interest to know how the more ergonomically feasible cycle training compares with treadmill training as therapy to manage SCI-induced spasticity and to improve locomotor function. Our present studies were initiated to evaluate the influence of different types of locomotor training on measures of limb spasticity, gait, and reflex components that contribute to locomotion. For these studies, thirty animals received midthoracic SCI using the standard MASCIS protocol (10 g 2.5 cm weight drop). They were divided randomly into three equal groups: control (contused untrained), contused treadmill trained, and contused cycle trained. Velocity-dependent ankle torque was tested across a wide range of velocities (612 – 49 deg/sec) to permit quantitation of tonic (low velocity) and dynamic (high velocity) contributions to lower limb spasticity. Treadmill and cycle training were started on post-injury day 8. By post-injury weeks 4 and 6, the untrained group revealed significant velocity-dependent ankle extensor spasticity, compared to pre-surgical control values. At these post-injury time points, spasticity was not observed in either of the two training groups. Instead, a significantly milder form of velocity dependent spasticity was detected at postcontusion week 8 through 12 in both treadmill and bicycle training groups at the four fastest ankle rotation velocities (350 - 612 deg/sec). Locomotor training using treadmill or bicycle also produced significant increase in the rate of recovery of limb placement measures (limb axis, base of support, and BBB) and reflex rate depression, a quantitative assessment of neurophysiological proce